Porovnání kvality nejčastěji používaných nových UHMWPE artikulačních vložek náhrady kyčelního kloubu - Fulín, P; Šlouf, M; Vlková, H; Krejčíková, S; Kredatusová, J; Pokorný, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY For an orthopedic surgeon it is difficult or even impossible to estimate the real quality of ultrahigh molecular weight polyethylene (UHMWPE) liners that are used in the total joint replacements (TJR) just on the basis of information given by the manufacturers. At the same time, the quality of the UHMWPE liner can impact strongly on the total lifespan of the implanted TJR. This work aims at independent, objective comparison of properties of the UHMWPE liners for total hip replacements (THR), which are most frequently used in the Czech Republic. MATERIAL AND METHODS We analyzed seventeen most frequently implanted UHMWPE cups of different manufacturers implanted in the Czech Republic between 2014 and 2015 and four control samples prepared by standard industrial-scale procedures according to our instructions, whose modification (crosslinking, thermal treatment, stabilization and sterilization) was known in detail. The UHMWPE polymer was characterized by four independent microscale methods, suitable for relatively small and irregular specimens such as THR cups: infrared microspectroscopy (IR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). RESULTS The employed methods yielded quite complete information about the investigated UHMWPE materials. IR spectra enabled us to calculate oxidation indexes (OI, measure of oxidative damage), trans-vinylene indexes (VI, measure of absorbed radiation dose during crosslinking and/or sterilization) and crystallinity indexes (CI, amount of crystalline phase that strongly influences mechanical performance). DSC curves were employed in calculation of crystallinities (wc, proportional to CI) and melting points (Tm, proportional to the average thickness of crystalline lamellae). MH measurements confirmed that the observed structure changes showed a real impact on mechanical properties. TGA experiments gave rough estimate of stabilization and, consequently, possible long-term oxidation resistance. Significant correlations among oxidative damage (OI), crystallinity (CI, wc) and microhardness (Hv) were statistically proven. The highest oxidative degradation was usually observed in samples thermally treated by annealing and/or sterilized by gamma irradiation. DISCUSSION The results confirmed our expectations that the UHMWPE liners from various manufacturers can be significantly different as far as their molecular structure, supermolecular structure, and mechanical properties are concerned. The differences among the various UHMWPE can be expected to increase after the implantation during in vivo. CONCLUSIONS From the clinical practice point of view, the results showed the following facts: (i) In the field of THR, all manufactures prefer crosslinked types of UHMWPE due to their increased wear resistance; non-crosslinked UHMWPEs are regarded as obsolete. (ii) Most of the manufacturers prefer ethylene oxide or gas plasma sterilization to gamma sterilization because the gammasterilized UHMWPEs exhibit lower long-term oxidation resistance. (iii) Modern trend is the stabilization of UHMWPEs with vitamin E. Key words: UHMWPE, hip replacements, oxidative degradation, infrared spectroscopy, microhardness.
Keywords: testování materiálů; Arthroplasty, Replacement, Hip; Materials Testing; polyethyleny; náhrada kyčelního kloubu; Humans; Česká republika; lidé; Polyethylenes; Czech Republic